2012
DOI: 10.1007/s00134-012-2791-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes and quality of life in critically ill patients with hematological or solid malignancies: a single center study

Abstract: Long-term outcomes and QOL were poor, particularly in HM. Long-term expectations should play a larger role during multidisciplinary triage decisions upon referral to the ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
118
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(133 citation statements)
references
References 37 publications
12
118
1
2
Order By: Relevance
“…113 In the ICU setting, few data are available for patients with hematological malignancies. 10,114,115 Studies are warranted to evaluate long-term outcome in allo-HSCT long-term ICU survivors. The place of patient and family wishes and implication in the shared decision-making process also needs to be clearly evaluated.…”
Section: Limitations Of the Published Experiences And Unresolved Issuesmentioning
confidence: 99%
“…113 In the ICU setting, few data are available for patients with hematological malignancies. 10,114,115 Studies are warranted to evaluate long-term outcome in allo-HSCT long-term ICU survivors. The place of patient and family wishes and implication in the shared decision-making process also needs to be clearly evaluated.…”
Section: Limitations Of the Published Experiences And Unresolved Issuesmentioning
confidence: 99%
“…A recent multicenter study suggested that the quality of life 90 days after ICU discharge in cancer patients was good and similar to age-and gender-matched cancer patients who did not require ICU admission [5]. In contrast, a previous study of critically ill cancer patients reported a profound alteration in quality of life up to 1 year following ICU admission [16]. The overall long-term survival of cancer patients after ICU discharge also remains largely unknown.…”
mentioning
confidence: 99%
“…There has been a very pervasive pessimism and scarcity of data on long-term outcomes after critical illness complicating hematological or solid malignancy. In a prospective, single-center observational study of 483 patients, Oeyen et al [53] assessed HRQoL outcomes at 3 months and 1 year after ICU discharge and compared these outcomes to HRQoL before ICU admission. Median age was 62 years and the majority were men with a solid malignancy.…”
Section: Quality Of Lifementioning
confidence: 99%